Pendampingan Perjalanan Wisata bagi Wisatawan Lanjut Usia sebagai Upaya Peningkatan Kualitas Hidup - Damiasih, Damiasih; Dewa, Parama Kartika; Budiman, Santi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Improving the quality of life of older adults is one of the important challenges in social development and public health. Older adults are vulnerable to boredom, decreased happiness, and limited social activities, especially after entering retirement. This community service activity aimed to provide education on the importance of tourism activities for older adults as a means of mental refreshment, increased happiness, and support for physical and mental health. The activity was conducted on October 19, 2025, at Glagah Beach, Kulon Progo Regency, involving 54 members of the Mandiri Sejahtera Association (Mandira) from the Karangkajen, Brontokusuman, and Mergangsan areas of Yogyakarta City. The methods used included lectures, question-and-answer sessions, interactive games, and assistance during tourism activities. The results showed that participants responded positively to the program. They appeared more enthusiastic, happier, and less bored, and gained new insights into the benefits of tourism for life in old age. The activity also created a more varied meeting atmosphere and enhanced social interaction among members. Based on these findings, it can be concluded that community service activities integrating education and tourism are effective in improving the psychological well-being and quality of life of older adults.